Creative Nostalgia: Social and Psychological Benefits of Scrapbooking. Issue 2 (3rd April 2021) - FioRito, Taylor A.; Geiger, Allie R.; Routledge, Clay
Abstract: Nostalgic memories are highly social and revisiting them increases social connectedness and motivation. The present study offers a naturalistic approach to studying the social experience of nostalgia. Participants created scrapbooks in groups across three sessions over a period of six weeks. Nostalgia proneness, meaning, and social connection were measured prior to the first and after the final session. A follow-up survey was also administered. Participants reported higher levels of nostalgia proneness and greater connectedness to their scrapbooking group following the sessions. The more participants reported experiencing negative psychological states, the more they indicated planning to use their scrapbooks as a source of psychological comfort. The present work has important implications for art therapists and arts in health practitioners.